AB0900 Serum uric acid level variations during gout attacks are linked neither to inflammation nor to uric acid fractional excretion: a prospective study of 35 patients. (15th June 2017) - Behar, V Masson; Desthieux, C; Aparicio, C; Manivet, P; Bardin, T; Richette, P; Lioté, F; Ostertag, A; Ea, H-K
Abstract : Background: Acute gout is usually associated with a decrease in serum uric acid (SUA) level but the mechanism responsible for this phenomenon remains unclear. Objectives: We aimed to investigate relationships between changes in SUA level, urinary excretion of uric acid and biochemical markers during gout attack. Methods: SUA, eGFR (estimated glomerular filtration rate), serum CRP level and urinary excretion of UA, expressed as fractional excretion of UA (FeUA), from 35 ULT (urate-lowering therapy)-free and diuretic-free gout patients were prospectively measured during acute gout attack (Tc) and intercritical (Tic) phase. In 11 patients, data were available after achievement of SUA target (Tt) (<360 μmol/l) under ULT. Demographics data and waist circumference (WC) were collected. Data are expressed as mean ± SD. Results: There were 32 men, mean age 57.9 years, mean body mass index 28.6 kg/m 2, and mean waist circumference 104 cm. Overall 17.1% had type 2 diabetes, 37.1% dyslipidemia, 54.3% hypertension, 34.4% obesity, 74.3% abdominal obesity and 51.4% chronic kidney disease (CKD, 31.4% CKD 2 and 20% CKD 3–5). Gout duration was 3.9±6.7 years, 28.6% of patients had tophus and 31.4% gout arthropathy. SUA, eGFR and FeUA values were similar between Tc and Tic phases: SUA: 504.9±79.9 and 507.6±89.7 μmol/l; eGFR: 78.1±28.8 and 81.4±33.8 ml/min/1.73m 2 ; FeUA: 4.90±2.3 and 4.45±3.3%, respectively. Moreover, the FeUA values were identical between Tt, Tic and Tc in 11 patients who achieved SUA target (296.0±37.8 μmol/l) under ULT. CRP levels were higher at Tc (44.8±69.4 mg/dL) than Tic (5.2±3.3 mg/dl) and Tt (4.6±1.2 mg/dl). While mean SUA levels were similar between Tc and Tic, SUA levels were lower in Tc than Tic in 21 patients (mean difference: 56.9±33.7 μmol/l) (figure1 ). In contrast, 14 patients had a SUA level higher in Tc than in Tic (mean difference: 78.6±71.5 μmol/L) (figure 1 ). SUA variations between Tc and Tic were not correlated with FeUA modifications in these two groups (p=0.15). Similarly, SUA and FeUA variations were not correlated with CRP variations between Tc and Tic (p=0.29 and p=0.30, respectively). Conclusions: SUA levels during gout attack can be either higher or lower than SUA during intercritical phase. These variations are linked neither to inflammation level nor to FeUA. It would be interesting to assess the intestinal excretion of uric acid, xanthine oxidase activity and diet intake during these different gout phases. Disclosure of Interest: None declared